2020
DOI: 10.1186/s13046-020-01629-4
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles and the regulation of aerobic glycolysis in hepatocellular carcinoma

Abstract: Liver cancer has become the sixth most diagnosed cancer and the fourth leading cause of cancer death worldwide. Hepatocellular carcinoma (HCC) is responsible for up to 75–85% of primary liver cancers, and sorafenib is the first targeted drug for advanced HCC treatment. However, sorafenib resistance is common because of the resultant enhancement of aerobic glycolysis and other molecular mechanisms. Aerobic glycolysis was firstly found in HCC, acts as a hallmark of liver cancer and is responsible for the regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
338
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(346 citation statements)
references
References 216 publications
7
338
0
1
Order By: Relevance
“…Although we found no differences in age, gender, T stage, N stage, AJCC stage, grade between glycolysis-H group and glycolysis-L group, the difference in M stage was obvious ( Table 1 ), which revealed that enhanced glycolytic activity facilitated invasion and metastasis in BLCA. This phenomenon was also revealed in pancreatic cancer [ 20 ], breast cancer [ 21 ], hepatocellular carcinoma [ 22 ], and gastric cancer [ 23 ].…”
Section: Resultsmentioning
confidence: 87%
“…Although we found no differences in age, gender, T stage, N stage, AJCC stage, grade between glycolysis-H group and glycolysis-L group, the difference in M stage was obvious ( Table 1 ), which revealed that enhanced glycolytic activity facilitated invasion and metastasis in BLCA. This phenomenon was also revealed in pancreatic cancer [ 20 ], breast cancer [ 21 ], hepatocellular carcinoma [ 22 ], and gastric cancer [ 23 ].…”
Section: Resultsmentioning
confidence: 87%
“…HK2 is a key enzyme associated with glycolysis, which contributes to multiple cell processes, like cell proliferation, invasion, migration, angiogenesis, and drug resistance in HCC. 36 Moreover, Huang et al showed that the up-regulation of HK2 increased glycolysis to promote cell migration and invasion in HCC. 37 Furthermore, multiple evidences suggested that HK2 could promote glycolysis and was responsible for migration and invasion in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence and progression of HCC are also closely intertwined with its metabolic disorders. Similar to most other solid tumors, the metabolic process of HCC cells has undergone many signi cant changes compared with normal liver cells, which are manifested in abnormally elevated glycolytic activity, increased de novo synthesis of fatty acids and decreased oxidation, as well as accelerated glutamine catabolism [2][3][4].…”
Section: Introductionmentioning
confidence: 99%